Exploring The Nexus Of Global Climate Changes And Infectious Disease Dynamics: A Depth Review Study (Journal of Namibian Studies : History Politics Culture, 2022)
Climate change refers to long-term changes in temperature, precipitation patterns and atmospheric variables on the Earth, which mostly result from human activities like deforestation and fossil fuel combustion. There are direct and indirect impacts of these environmental shifts on the well-being of individuals and communities, posing an imminent threat to global human health. Surviving calamities like floods, wildfires, etc. is an area of concern for the healthcare system. Moreover, in the recent years, research has shown a significant change in the transmission dynamics of infectious diseases due to weather extremes, air quality deterioration, rising sea levels, scarcity of water resources and altered food production systems. Activities related with deforestation are also major contributors to the spread of infectious disease vectors. The rise in drug and insecticide resistance has further intensified the risk of infectious diseases in both, humans and animals. A recent meta-analysis has reported that more than 50% of known human pathogens are anticipated to be augmented due to climate change. Further research progress is warranted in this area to bridge the gaps and execute strategies for adapting to the changing climatic conditions. In this article, we provide insights into the impacts of global climate change on the rising infectious disease conditions in humans. The paper shall discuss the current trends, challenges and opportunities persisting in this field of study and provide a comprehensive review to the readers.